Evaluation of Proposed In Vivo Probe Substrates and Inhibitors for Phenotyping Transporter Activity in Humans - Momper, Jeremiah D; Tsunoda, Shirley M; Ma, Joseph D (Journal of clinical pharmacology, 2016)
Drug transporters are present in various tissues and have a significant role in drug absorption, distribution, and elimination. The International Transporter Consortium has identified 7 transporters of increasing importance from evidence of clinically significant transporter-mediated drug-drug interactions. The transporters are P-glycoprotein, breast cancer resistance protein, organic anion transporting polypeptide (OATP) 1B1, OATP1B3, organic cation transporter 2, organic anion transporters (OAT) 1, and OAT3. Decision trees were created based on in vitro experiments to determine whether an in vivo transporter-mediated drug-drug interaction study is needed. Phenotyping is a methodology that evaluates real-time in vivo transporter activity, whereby changes in a probe substrate or probe inhibitor reflect alternations in the activity of the specified transporter. In vivo probe substrates and/or probe inhibitors have been proposed for each aforementioned transporter. In vitro findings and animal models provide the strongest evidence regarding probe specificity. However, such findings have not conclusively correlated with human phenotyping studies. Furthermore, the extent of contribution from multiple transporters in probe disposition complicates the ability to discern if study findings are the result of a specific transporter and thus provide a recommendation for a preferred probe for a drug transporter.